Protes dan Roh Kudus: Sebuah Upaya Awal dalam Membangun Hubungan Teologis - Cinema, Richardo (Indonesian Journal of Theology, 2025)
This article examines protest as pneumatological praxis that has so far received little recognition within Christian theology. A review of two major approaches—protest to God and protest to others—shows that protest is often understood symbolically and not as a public practice of Christianity. Precedent research also indicates that protest against the government is often instrumental, rather than an integral expression of faith. This article argues that protests against institutions can be understood as an ecclesial praxis supported by the Holy Spirit. Through a philosophical approach to protest (Clayton Bohnet and Sara Ahmed) and a Third Article Theology characterization of the Holy Spirit (Myk Habets and Gregory J. Liston), protest is interpreted as a pneumatological act rooted in the church's liturgy. Through protest, the church is politically present in the public sphere as an expression of fidelity to the Holy Spirit's work in a suffering world